2012
DOI: 10.1128/cvi.00268-12
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Function of Antibodies to Pneumococcal Surface Protein A but Not to Capsular Polysaccharide in Mexican American Adults with Type 2 Diabetes Mellitus

Abstract: ABSTRACTThe goal of the study was to determine baseline protective titers of antibodies toStreptococcus pneumoniaesurface protein A (PspA) and capsular polysaccharide in individuals with and individuals without type 2 diabetes mellitus. A total of 561 individuals (131 individuals with diabetes and 491 without) were screened for antibodies to PspA using a standard enzyme-linked immunosorbent assay (ELISA). A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…There are data supporting alterations in complement receptors or complement function in DM or hyperglycemia. In diabetics there appears to be a lower percentage of CR3-positive monocytes, and in a separate study anti-PspA antibodies to S. pneumonia displayed reduced capacity for C3 deposition that was proportional to glucose control 16;17 Hyperglycemia has been associated with induction of structural changes on C3 that inhibit C3-mediated effector functions to S. aureus . 40 We are beginning to assess if there are defects in the complement components in serum and monocytes that explain the reduced association of M. tuberculosis , but we cannot exclude abnormalities in other heat-labile components of the immune system, such as cytokines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are data supporting alterations in complement receptors or complement function in DM or hyperglycemia. In diabetics there appears to be a lower percentage of CR3-positive monocytes, and in a separate study anti-PspA antibodies to S. pneumonia displayed reduced capacity for C3 deposition that was proportional to glucose control 16;17 Hyperglycemia has been associated with induction of structural changes on C3 that inhibit C3-mediated effector functions to S. aureus . 40 We are beginning to assess if there are defects in the complement components in serum and monocytes that explain the reduced association of M. tuberculosis , but we cannot exclude abnormalities in other heat-labile components of the immune system, such as cytokines.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown reduced phagocytosis of neutrophils to extracellular pathogens, including Streptococcus pneumonia , Staphylococcus aureus , Escherichia coli , S. epidermidis and Candida spp. 17;3739 In contrast, there are few studies with monocytes, but all show reduction in phagocytosis to different pathogens (opsonized Eschelichia coli , Candida albicans and Listeria monocytogenes ) 10;15;23 Whether the underlying defect for phagocytosis is in type 1 or type 2 DM, or in PMN versus monocytes is unclear, with alterations attributed to serum factors, the phagocyte, or both, depending on the study. Our findings suggest that reduced M. tuberculosis association may be related to altered complement in serum or complement receptors in monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the absence of glucose in the nasopharynx of colonized adults may help to explain why colonization does not typically result in an overt inflammatory state. Additionally, increases in glucose concentration within the nasopharynx-for example, as a result of virusinduced inflammation or even uncontrolled diabetes-may further explain why individuals with these conditions are vulnerable to IPD (62,64,65). Thus, catabolite repression is possibly a key event in initiating a pathogenic program of S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia has been suggested to cause structural changes in C3b that lead to reduced phagocytosis of E. coli [37] in DM2 patients and antibodies show significantly higher glycation when compared to non-DM2 controls but the impact of these findings on function is unclear [38], [39]. Among Hispanics, those with DM2 had lower antibody titers and reduced opsonophagocytosis of S. pneumoniae [40].…”
Section: Discussionmentioning
confidence: 99%